Peran Manajemen Public Relations PT. Airasia Indonesia Tbk dalam Mempertahankan Citra Perusahaan - Raida, Astrid Marliana; Salsabilla, Salwa; Mansoer, Faizah Kamilla; Patrianti, Tria (PT Literasi Nusantara Publisher, 2024)
Public Relations Management is one of the main keys in maintaining and improving the company's strategy to create a positive image, build good relations with the public, and can overcome the threats and challenges that exist in the aviation industry. This research discusses how the role of Public Relations Management of PT AirAsia Tbk in dealing with the incident of the crash of AirAsia QZ8501 aircraft flying from Surabaya to Singapore. In handling crisis situations, the speed of response will greatly affect public loyalty to a company. The purpose of this research is to identify the role of Public Relations Management of PT AirAsia Indonesia Tbk in maintaining the image and focus research on issues that have been circulating. The research method used is a qualitative approach with a case study method, with stages: 1) Analyzing all information on social media owned by AirAsia Tbk. 2) Information search by analyzing AirAsia's press releases related to the crash of flight QZ8501 as well as documentary evidence of AirAsia that appeared in various media. 3) Literature study to better understand the role of Public Relations Management carried out by AirAsia. Through this research, AirAsia showed a good response in dealing with the crisis by prioritizing the victims and the families of the victims, being transparent to the public, the media became the main channel in establishing communication with the public through the CEO of AirAsia Tbk as the spokesperson of the company and making the crisis as material for company evaluation.